Birth Timing and Spacing: Implications for Parental Leave Dynamics and Child Penalties - Abi Adams-Prassl; Mathias Fjællegaard Jensen; Barbara Petrongolo (Institute of Labor Economics (IZA), 2024)
We develop new facts on relationships between the timing and spacing of births, parental leave take-up, and labor market outcomes using Danish administrative data. We document substantial heterogeneity in age at first birth across maternal skill levels. Average spacing of pregnancies is also tighter for highly skilled mothers, resulting in higher fertility levels and time on parental leave soon after first birth. We estimate event studies by skill level and find that much of child penalties in earnings and participation after first birth can be explained by incapacitation effects from parental leave around subsequent births, especially for the highly educated.
Keywords: J13; J16; 330; fertility; child penalty; skill